2015
DOI: 10.1111/jam.12772
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic L actobacillus rhamnosus GR ‐1 and L actobacillus reuteri RC ‐14 exhibit strong antifungal effects against vulvovaginal candidiasis‐causing C andida glabrata isolates

Abstract: AimsThis study investigates the antagonistic effects of the probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 against vulvovaginal candidiasis (VVC)-causing Candida glabrata.Methods and ResultsGrowth inhibitory activities of Lact. rhamnosus GR-1 and Lact. reuteri RC-14 strains against C. glabrata were demonstrated using a spot overlay assay and a plate-based microtitre assay. In addition, these probiotic lactobacilli strains also exhibited potent candidacidal activity against C. gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 37 publications
2
56
0
2
Order By: Relevance
“…Candida albicans was found to be more susceptible to the antifungal effect of Lactobacillus than C. tropicalis [27]. Moreover, probiotic bacteria and their supernatant also exhibited growth inhibitory activities against C. glabrata [32]. The production of hydrogen peroxide by the probiotics that antagonize candidal growth was a notable phenomenon observed in a number of these studies [27,30].…”
Section: In Vitro Evidence Of the Antifungal Effects Of Probioticsmentioning
confidence: 87%
See 2 more Smart Citations
“…Candida albicans was found to be more susceptible to the antifungal effect of Lactobacillus than C. tropicalis [27]. Moreover, probiotic bacteria and their supernatant also exhibited growth inhibitory activities against C. glabrata [32]. The production of hydrogen peroxide by the probiotics that antagonize candidal growth was a notable phenomenon observed in a number of these studies [27,30].…”
Section: In Vitro Evidence Of the Antifungal Effects Of Probioticsmentioning
confidence: 87%
“…Studies using antagonism in agar diffusion assays have demonstrated that Lactobacillus species inhibit the growth of both gram-positive and gram-negative pathogens (eg, Streptococcus mutans and Escherichia coli, respectively) [13,14], in addition to Candida species [13,14,25,27,30,32]. Candida albicans was found to be more susceptible to the antifungal effect of Lactobacillus than C. tropicalis [27].…”
Section: In Vitro Evidence Of the Antifungal Effects Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in metabolically active cells, formation of orange cylindrical structures designated CIVS (Cylindrical IntraVacuolar Structures) is observed inside vacuoles. CIVS formation only occurs in metabolically active cells with an intact plasma membrane, meaning they are not observed in dead cells (Chew et al, 2015). Calcofluor white is a compound with high affinity to chitin and is normally used as a marker of the fungal cell wall.…”
Section: Resultsmentioning
confidence: 99%
“…The native bacterial flora, which is often dominated by Lactobacillus spp., maintains a low pH and exerts a fungistatic effect against Candida spp. (Parolin et al, 2015, Chew et al, 2015, Hutt et al, 2016). In addition, certain Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%